DOI: 10.11606/t.44.2016.tde-28092016-135646
|View full text |Cite
|
Sign up to set email alerts
|

Revisão sistemática e paleobiogeográfica de Trilobitas Phacopida (Homalonotidae e Calmoniidae) do Devoniano das Bacias do Parnaíba e Amazonas, Brasil

Abstract: iv teria se dado a sudoeste desta bacia, já que Malvinella ocorre apenas nesta bacia e na Bolívia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…venusta (Carvalho and Ponciano, 2015). In the Homalonotidae family, only Burmeisteria notica has been identified (Leme et al, 2013;Meira, 2014), with a width range of 22-40 mm (Leme et al, 2013), similar to the mean width of the Rusophycus specimens studied here (~35 mm). The sizes of the Metacryphaeus species differ, with M. kegeli being the smallest, ranging widthwise from ~7 to 23 mm (Carvalho et al, 1997), M. meloi ranging in width from ~17 to 31 mm (Carvalho et al, 1997;Leme et al, 2013), and M. tuberculatus ranging in width from approximately from 30 to 108 mm, with some complete specimens ranging lengthwise from 75 to 176 mm (Carvalho et al, 1997;Meira et al, 2016).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…venusta (Carvalho and Ponciano, 2015). In the Homalonotidae family, only Burmeisteria notica has been identified (Leme et al, 2013;Meira, 2014), with a width range of 22-40 mm (Leme et al, 2013), similar to the mean width of the Rusophycus specimens studied here (~35 mm). The sizes of the Metacryphaeus species differ, with M. kegeli being the smallest, ranging widthwise from ~7 to 23 mm (Carvalho et al, 1997), M. meloi ranging in width from ~17 to 31 mm (Carvalho et al, 1997;Leme et al, 2013), and M. tuberculatus ranging in width from approximately from 30 to 108 mm, with some complete specimens ranging lengthwise from 75 to 176 mm (Carvalho et al, 1997;Meira et al, 2016).…”
Section: Discussionsupporting
confidence: 76%
“…10.3389/fevo.2023.1117947 Frontiers in Ecology and Evolution 09 frontiersin.org as the main tracemaker of the studied Rusophycus specimens, mostly during the molting phase. However, the Parnaíba Basin has a limited record of trilobites, with only few species from the Calmonidae and Homalonotidae families (Ghilardi and Simões, 2007;Meira, 2014;Carbonaro et al, 2018). The most common genus within Calmonidae is Metacryphaeus, with three species recorded: M. tuberculatus, M. meloi, and M. kegeli (Carvalho et al, 1997;Leme et al, 2013;Meira, 2014;Meira et al, 2016;Carbonaro et al, 2018), along with a record of Eldredgeia cf.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed results similar to these, with 22.71% of fetal deaths having intrauterine hypoxia as the registered cause and 20.8% as death without explanation 19 . Jacinto et al 20 found intrauterine hypoxia as the cause of fetal death in 44.7% of cases.…”
Section: Discussionsupporting
confidence: 72%